Evaluation of UV and visible light activity of TiO2 catalysts for water remediation - Manassero, Agustina (2013)
The photocatalytic activity under UV, visible and UV-visible radiation of two commercial catalysts for water remediation are evaluated and compared in a slurry reactor. Bisphenol A (BPA) was employed as the model pollutant. The activities of the carbon-doped, TiO2 catalyst Kronos vlp 7000 and, as a reference, the undoped catalyst Aeroxide P25 are compared by means of efficiency parameters: the overall photonic efficiency and the quantum efficiency. For the evaluation of the radiation absorbed by the catalyst suspensions, the optical properties of TiO2 Kronos vlp 7000 between 300 and 550 nm were measured and reported, as well as the properties of TiO2 Aeroxide P25 in the range 400?550 nm. Kronos catalyst exhibits absorption in the visible range and was almost three times more efficient than Aeroxide for BPA degradation under this condition. However, under UV radiation, Aeroxide P25 quantum efficiency was about 1.5 times the corresponding value of Kronos. Similar BPA photonic and quantum efficiencies were obtained under UV-visible radiation with both commercial catalysts.